Challenges and Benefits of Learning Business English: A Learner-Centered Case Study at Madyathika Polytechnic - Artika Wina Fitriani; Actinis Muqsitha Paradista (Haumeni Journal of Education, 2026)
This research explores the challenges and benefits of learning Business English from a learner-centered perspective, specifically at Madyathika Polytechnic. In today’s global environment, English is vital in the workplace, particularly in business, elevating its importance in higher education, especially vocational schools. Despite gaining valuable skills, students face significant challenges such as limited business vocabulary, lack of speaking confidence, insufficient real-world material exposure, and varying English proficiency levels. The research involved the second semester students of the Madyathika Polytechnic as the participants. This research uses a qualitative case study method to understand students’ experiences. The data were collected through interviews, classroom observations, and document analysis involving selected students. However, the findings indicate that learning business English has significant advantages for pupils. They enhance their communication skills, boost confidence in professional English settings, and feel better prepared for future jobs. Engaging in discussions, role-plays, and real-world simulations fosters student motivation and engagement.